Condições de trabalho docente como diferencial no desempenho de alunos no ENEM no triênio 2016-2018 - Santos, Bernardo Augusto Farah (2020)
Among the many factors that influence working conditions, the low remuneration of teachers has always been a challenge of Brazilian education. This work aims to analyze the relationship between teacher remuneration and the results obtained by the high school students from the state and federal systems of the state of Minas Gerais. For that, was held a search from the official data provided by the Ministry of Education, as well as observing the laws governing the contract of teachers. Data analysis revealed that teachers with lower pay and less incentive to continuing education are in the state school system. This fact induces the search of alternatives sources of income, which overloads the professional. This reality may be related with the different results in the National High School Examination of students from the state system when compared to the federal education system, where the teachers receive better salaries and incentive to specialization.